2011
DOI: 10.1371/journal.pone.0017507
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of TGF-β1, Fascin, NF-κB and PKC-ζ Expression in Soft Tissue Sarcomas

Abstract: AimsTransforming growth factor-β (TGF-β), fascin, nuclear factor-kappa B (NF-κB) p105, protein-kinase C-zeta (PKC-ζ), partioning-defective protein-6 (Par-6), E-cadherin and vimentin are tumor promoting molecules through mechanisms involved in cell dedifferentiation. In soft tissue sarcomas, their expression profile is poorly defined and their significance is uncertain. We aimed to investigate the prognostic impact of TGF-β1, NF-κB p105, PKC-ζ, Par-6α, E-cadherin and vimentin in non-gastrointestinal stromal tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…However, several recent reports have implicated PKCζ as a predictor of poor outcome for cancer patients. High PKCζ predicts poor disease-specific survival of patients with soft tissue sarcoma [39]. Likewise, PKCζ is elevated in prostate cancer, and high PKCζ expression predicts poor survival of prostate cancer patients [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several recent reports have implicated PKCζ as a predictor of poor outcome for cancer patients. High PKCζ predicts poor disease-specific survival of patients with soft tissue sarcoma [39]. Likewise, PKCζ is elevated in prostate cancer, and high PKCζ expression predicts poor survival of prostate cancer patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…While PKCζ expression has been recently characterized to be elevated and predict poor survival in several cancers [36], [39], little is known about the regulation of PKCζ expression. However, PKCζ has been shown to be activated by several signaling pathways known to promote oncogenic signaling in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to differences in expression of sexual hormone receptors (ER and PGR) in male and female STS patients [7,8]. In previous studies, we have shown the prognostic value of female steroid hormone receptors in STSs, both alone and in coexpression with TGF-β, fascin and Akt isoforms [7-9]. Such prognostic impact is not surprising, since both ER and PGR regulate growth and cell differentiation upon ligand-dependent and ligand-independent activation and are in essence growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…PBS (phosphate buffer saline) was used in replacement of primary antibody as a blank control. The section was considered as expressing the protein if cellular staining ≥5%, following the methods described previously [26, 27]. …”
Section: Methodsmentioning
confidence: 99%